Fluorine-18: Radiochemistry and Target-Specific PET Molecular Probes Design - Wang, Yunze; Lin, Qingyu; Shi, Hongcheng; Cheng, Dengfeng (Frontiers in chemistry, 2022)
The positron emission tomography (PET) molecular imaging technology has gained universal value as a critical tool for assessing biological and biochemical processes in living subjects. The favorable chemical, physical, and nuclear characteristics of fluorine-18 (97% β + decay, 109.8 min half-life, 635 keV positron energy) make it an attractive nuclide for labeling and molecular imaging. It stands that 2-[ 18 F]fluoro-2-deoxy-D-glucose ([ 18 F]FDG) is the most popular PET tracer. Besides that, a significantly abundant proportion of PET probes in clinical use or under development contain a fluorine or fluoroalkyl substituent group. For the reasons given above, 18 F-labeled radiotracer design has become a hot topic in radiochemistry and radiopharmaceutics. Over the past decades, we have witnessed a rapid growth in 18 F-labeling methods owing to the development of new reagents and catalysts. This review aims to provide an overview of strategies in radiosynthesis of [ 18 F]fluorine-containing moieties with nucleophilic [ 18 F]fluorides since 2015.